Pharmacokinetics of rectal levetiracetam as add-on treatment in dogs affected by cluster seizures or status epilepticus - Cagnotti, Giulia; Odore, Rosangela; Gardini, Giulia; Amedeo, Stefano; Bertone, Iride; Guerriero, Giulia; Lentini, Laura; Dappiano, Elena; D’Angelo, Antonio (BMC veterinary research, 2018)
Background Levetiracetam can be used for seizure control alone or in combination with other antiepileptic medications. A previous study achieved the minimum targeted serum drug concentration after rectal administration of levetiracetam in healthy dogs. The purpose of the present study was to determine the pharmacokinetics of rectal LEV in dogs presented for cluster seizures or status epilepticus and potentially in treatment with other anti-epileptic drugs. Furthermore, preliminary information on response to this treatment as add-on to the standard treatment protocol is reported. Results Eight client-owned dogs were enrolled. Plasma levetiracetam concentrations (measured at 0, 30, 60, 90, 120, 180, 240, 360, 720, and 1440 min after drug administration) reached the minimum target concentration (5 μg/ml) at 30 min in all but one patient. At T1 (30 min) the mean concentration was 28.2 ± 15.5 μg/ml. Plasma concentrations remained above the targeted minimum concentration in all patients until 240 min and in 7/8 until 360 min. Six out of eight patients experienced no seizures in the 24-h period after hospitalization and were classified as “responders”. Conclusions Minimum plasma levetiracetam concentration can be reached after rectal administration of 40 mg/kg in dogs affected by cluster seizures and status epilepticus and concurrently receiving other antiepileptic drugs. These preliminary results may encourage the evaluation of rectal levetiracetam as an additional treatment option for cluster seizures and status epilepticus in a larger number of dogs.